2020
DOI: 10.1021/acs.jmedchem.0c01635
|View full text |Cite
|
Sign up to set email alerts
|

Acylated 1H-1,2,4-Triazol-5-amines Targeting Human Coagulation Factor XIIa and Thrombin: Conventional and Microscale Synthesis, Anticoagulant Properties, and Mechanism of Action

Abstract: We herein report the conventional and microscale parallel synthesis of selective inhibitors of human blood coagulation factor XIIa and thrombin exhibiting a 1,2,4-triazol-5-amine scaffold. Structural variations of this scaffold allowed identifying derivative 21i, a potent 29 nM inhibitor of FXIIa, with improved selectivity over other tested serine proteases and also finding compound 21m with 27 nM inhibitory activity toward thrombin. For the first time, acylated 1,2,4-triazol-5-amines were proved to have antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
111
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(122 citation statements)
references
References 75 publications
0
111
1
Order By: Relevance
“…The unbound fragments FR1 and FR2 (shown as orange and green figures) and the coupling reagents (shown as X‐ and square‐shaped figures) are low active or inactive inhibitors of FXIIa and thrombin and do not interfere with the assay at low concentrations (Figure 4, A). We previously showed that the unbound fragments FR1 and FR2 cannot efficiently inhibit the enzymes as only connected fragments (FR1‐FR2) are capable of covalent interaction with the enzymes’ catalytic Ser195 (also see the “Mechanism of Inhibition” section) [3f] . Accordingly, when FR1 and FR2 are bound to each other forming N‐acylated aminotriazole, a significant shift in inhibitory activity is observed (toward lower doses, Figure 4, B).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…The unbound fragments FR1 and FR2 (shown as orange and green figures) and the coupling reagents (shown as X‐ and square‐shaped figures) are low active or inactive inhibitors of FXIIa and thrombin and do not interfere with the assay at low concentrations (Figure 4, A). We previously showed that the unbound fragments FR1 and FR2 cannot efficiently inhibit the enzymes as only connected fragments (FR1‐FR2) are capable of covalent interaction with the enzymes’ catalytic Ser195 (also see the “Mechanism of Inhibition” section) [3f] . Accordingly, when FR1 and FR2 are bound to each other forming N‐acylated aminotriazole, a significant shift in inhibitory activity is observed (toward lower doses, Figure 4, B).…”
Section: Resultsmentioning
confidence: 85%
“…The resultant library of compounds was screened against FXIIa and thrombin revealing potent dual and selective inhibitors of FXIIa and/or thrombin. The results of this screening have been disclosed by us earlier and will not be repeated here [3f] . The screening was limited only to the variations on the inhibitors’ acyl fragment (FR2), leaving the aminotriazole core (FR1) unchanged and therefore unexplored.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations